Children of Chicago - Pelayo, Cynthia (Agora Books, 2021)
"When Detective Lauren Medina sees the calling card at a murder scene in Chicago's Humboldt Park neighborhood, she knows the Pied Piper has returned. When another teenager is brutally murdered at the same lagoon where her sister's body was found floating years before, she is certain that the Pied Piper is not just back, he's looking for payment he's owed from her. Lauren's torn between protecting the city she has sworn to keep safe, and keeping a promise she made long ago with her sister's murderer. She may have to ruin her life by exposing her secrets and lies to stop the Pied Piper before he collects."--Publisher.